Office 2010 Made Simple - Hart-Davis, Guy; Made Simple Learning, MSL (Apress : Imprint: Apress, 2011)
Office 2010 Made Simple for Windows is a practical and highly effective approach to using the Office 2010 Home & Business (Word, Excel, PowerPoint, Outlook, OneNote) and Home & Student (Word, Excel, PowerPoint, OneNote) programs to create and edit documents and get work done efficiently. Conveying information quickly and concisely, the book brings you from a beginner or low intermediate to an experienced and confident user. Illustrated graphical approach shows what happens at each stage Short sections provide instant access to each task the reader needs to perform Step-by-step instructions help the reader grasp even complex procedures in full confidence.